Abnormal neurobehaviour and impaired memory function as a consequence of Toxocara canis- as well as Toxocara cati-induced neurotoxocarosis. - Elisabeth Janecek; Patrick Waindok; Marion Bankstahl; Christina Strube (Public Library of Science (PLoS), 2017)
Neuroinvasive larvae of the worldwide occurring zoonotic roundworms Toxocara canis and T. cati may induce neurotoxocarosis (NT) in humans, provoking a variety of symptoms including cognitive deficits as well as neurological dysfunctions. An association with neuropsychological disorders has been discussed. Similar symptoms have been described in T. canis-infected mice, whereas data on T. cati-induced NT are rare. Therefore, it was aimed to obtain insights into the impact on neurobehaviour as well as progression of neurological symptoms and behavioural alterations during the course of NT directly comparing T. canis- and T. cati-infected mice as models for human NT.C57BL/6 mice were orally infected with 2000 embryonated T. canis or T. cati eggs, respectively, the control group received tap water. Mice were screened weekly for neurobehavioural alterations and memory function starting one day prior infection until 97 days post infection (pi; T. canis-infection) and day 118 pi (T. cati-infection, uninfected control). Mostly motoric and neurological parameters were affected in T. canis-infected mice starting day 20 pi with severe progression accompanied by stereotypical circling. In contrast, T. cati-infected mice mostly showed reduced response to sudden sound stimulus (indicator for excitability) and flight behaviour starting day 6 pi. Interestingly, enhanced grooming behaviour was observed exclusively in T. cati-infected mice, indicating a possible role of neurotransmitter dysregulation. Reduced exploratory behaviour and memory impairment was observed in both infection groups with delayed onset and less severe progression in T. cati- compared to T. canis-infected mice.Results highlight the need to consider T. cati beside T. canis as causative agent of human NT. Findings provide valuable hints towards differences in key regulatory mechanisms during T. canis- and T. cati-induced NT, contributing to a comprehensive picture and consequently a broader understanding of NT, which will aid in developing strategies towards prevention in addition to novel diagnostic and therapeutic approaches.